Psychosocial health is associated with objectively assessed sedentary time and light intensity physical activity among lung cancer survivors - Vallance, J.; Bebb, G.; Boyle, Terry; Johnson, S.; Gardiner, P.; D'Silva, A. (Elsevier BV, 2018)
Statement of problem: Lung cancer survivors report among the highest levels of depression and anxiety compared to other tumor groups. To date, no studies have examined associations of accelerometer-assessed activity and sedentary time with psychosocial health outcomes among lung cancer survivors. The objective of this study was to determine associations of accelerometer-assessed light intensity physical activity, moderate-to-vigorous intensity physical activity (MVPA), and sedentary time with psychosocial health among lung cancer survivors. Method: Lung cancer survivors in Southern Alberta completed a mailed survey that assessed measures of depressive symptoms (PHQ-9; Patient Health Questionnaire-9: range = 0-27), anxiety (State Anxiety Inventory: range = 10-40), satisfaction with life (SWL; Satisfaction With Life Scale: range = 5-35), and posttraumatic growth (PTG; Posttraumatic Growth Inventory: range = 0-105). Participants also wore an Actigraph® GT3X + accelerometer for seven days. Quantile regression was used to examine associations of depression, anxiety, SWL, and PTG with light intensity physical activity, MVPA, and sedentary time. Results: A total of 127 lung cancer survivors participated for a 24% response rate. Total sedentary time min/day was associated with depressive symptoms at the 50th percentile (β = 0.02, 95% CI: 0.0–0.03), SWL at the 25th percentile (β = -0.04, 95% CI: -0.07-0.0) and 50th percentile (β = -0.03, 95% CI: -0.05 to -0.01). Total light-intensity physical activity mins/day was associated with SWL at the 25th (β = 0.04, 95% CI: 0.00–0.07) and 50th (β = 0.03, 95% CI: 0.0–0.05) percentiles, and depressive symptoms at the 50th percentile (β = -0.02, 95% CI: -0.03-0.00). Total MVPA min/day was not associated with any psychosocial health outcomes. Conclusions: Sedentary time and light intensity physical activity were significantly associated with some psychosocial health outcomes. Reducing sedentary time and increasing light intensity physical activity may be a more appropriate recommendation for many lung cancer survivors given their older age, poorer functional status, and reduced pulmonary capacity.